2020
DOI: 10.1038/s41467-020-15963-w
|View full text |Cite|
|
Sign up to set email alerts
|

Apolipoprotein J is a hepatokine regulating muscle glucose metabolism and insulin sensitivity

Abstract: ✉Crosstalk between liver and skeletal muscle is vital for glucose homeostasis. Hepatokines, liver-derived proteins that play an important role in regulating muscle metabolism, are important to this communication. Here we identify apolipoprotein J (ApoJ) as a novel hepatokine targeting muscle glucose metabolism and insulin sensitivity through a low-density lipoprotein receptor-related protein-2 (LRP2)-dependent mechanism, coupled with the insulin receptor (IR) signaling cascade. In muscle, LRP2 is necessary for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 61 publications
0
46
0
Order By: Relevance
“…Male LRP1 loxP/loxP mice and AgRP-Cre; LRP1 loxP/loxP mice at 8 wk of age were used for GTT and ITT. The area under the curve or above the curve for glucose was calculated using the trapezoidal rule for GTT or ITT (29).…”
Section: Glucose Tolerance and Insulin Tolerance Testmentioning
confidence: 99%
“…Male LRP1 loxP/loxP mice and AgRP-Cre; LRP1 loxP/loxP mice at 8 wk of age were used for GTT and ITT. The area under the curve or above the curve for glucose was calculated using the trapezoidal rule for GTT or ITT (29).…”
Section: Glucose Tolerance and Insulin Tolerance Testmentioning
confidence: 99%
“…Since we found that increased CLU levels in pancreas and liver from the tissue specific CLU Tg mice do not induce premature onset of diabetes but exacerbate INS intolerance, we suggest that pancreas specific CLU upregulation may result in deregulation of the GLU-INS metabolic pathway. In support, CLU was identified recently as a hepatokine that targets muscle (a tissue particularly enhanced in males) GLU metabolism and INS sensitivity through low-density lipoprotein receptor-related protein-2 along with the INS receptor signaling cascade [ 22 ]. Elevated GLU levels upregulate the metabolic genes akt , foxo1 , pgc-1 , g6pc and pepck in the liver, where activation of the phosphoinositol 3-kinase/AKT pathway inhibits the rate-controlling enzymes of gluconeogenesis and promotes glycogen synthesis [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Secretory clusterin is also known as ApoJ. ApoJ has recently been identified as a novel hepatokine, and deletion of hepatic ApoJ leads to insulin resistance and glucose tolerance[28]. Furthermore, in humans, serum ApoJ levels correlate directly with increases in insulin resistance and these levels decrease in response to rosiglitazone treatment[29].…”
Section: Discussionmentioning
confidence: 99%